Impediments to Kindergarten Children Identifying Geometric Shapes - Vorkapić, Marija; Milinković, Jasmina Milinković; Milošević, Mila Milošević (Revija za elementarno izobraževanje, 2024)
Research shows that children aged 3 to 6 years do not fully grasp the concept of geometric shapes. This paper aims to examine children’s intuitive knowledge of triangles and squares. We analysed the effects of distractors on identification and the neglected properties of (non)examples. The purpose of the study was to establish the developmental path in the identification of shapes. It was operationalized by determining types of interfering distractors in shape recognition and properties neglected. The data obtained from individual interviews were processed by the method of statistical and descriptive qualitative analysis. A classification was made of distractors and properties of non-examples affecting identification.